Trade-offs in defence to pathogen species revealed in expanding nematode populations - Ordovas-Montanes, M; Preston, G; Hoang, K; Rafaluk-Mohr, C; King, KC (Wiley, 2022)
Many host organisms live in polymicrobial environments and must respond to a diversity of pathogens. The degree to which host defences towards one pathogen species affect susceptibility to others is unclear. We used a panel of Caenorhabditis elegans nematode isolates to test for natural genetic variation in fitness costs of immune upregulation and pathogen damage, as well as for tradeoffs in defence against two pathogen species, Staphylococcus aureus and Pseudomonas aeruginosa. We examined the fitness impacts of transient pathogen exposure (pathogen damage and immune-upregulation) or exposure to heat-killed culture (immune-upregulation only) by measuring host population sizes, which allowed us to simultaneously capture changes in reproductive output, developmental time, and survival. We found significant decreases in population sizes for hosts exposed to live versus heat-killed S. aureus and found increased reproductive output after live P. aeruginosa exposure, compared to the corresponding heat-killed challenge. Nematode isolates with relatively higher population sizes after live P. aeruginosa infection produced fewer offspring after live S. aureus challenge. These findings reveal that wild C. elegans genotypes display a trade-off in defences against two distinct pathogen species that are evident in subsequent generations.